2019
DOI: 10.3390/nu11040888
|View full text |Cite
|
Sign up to set email alerts
|

Theobromine Improves Working Memory by Activating the CaMKII/CREB/BDNF Pathway in Rats

Abstract: Theobromine (TB) is a primary methylxanthine found in cacao beans. cAMP-response element-binding protein (CREB) is a transcription factor, which is involved in different brain processes that bring about cellular changes in response to discrete sets of instructions, including the induction of brain-derived neurotropic factor (BDNF). Ca2+/calmodulin-dependent protein kinase II (CaMKII) has been strongly implicated in the memory formation of different species as a key regulator of gene expression. Here we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 95 publications
1
32
0
Order By: Relevance
“…After blood collection, 0.5 mL of blood sample was immediately used for blood cell counts. The following variables were measured in the CN and HE groups using a KX-21NV automatic hemocytometer (Sysmex, Kobe, Japan) as described previously [52,54]: WBC, RBC, PLT, HGB, HTC, MCH, MCHC and MCV. After blood cell counts, approximately 3.5 ml of blood was centrifuged (1500× g) for 20 min at 4 • C. Plasma was collected, flash frozen in liquid nitrogen and stored at −80 • C until use.…”
Section: Blood Cell Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…After blood collection, 0.5 mL of blood sample was immediately used for blood cell counts. The following variables were measured in the CN and HE groups using a KX-21NV automatic hemocytometer (Sysmex, Kobe, Japan) as described previously [52,54]: WBC, RBC, PLT, HGB, HTC, MCH, MCHC and MCV. After blood cell counts, approximately 3.5 ml of blood was centrifuged (1500× g) for 20 min at 4 • C. Plasma was collected, flash frozen in liquid nitrogen and stored at −80 • C until use.…”
Section: Blood Cell Countsmentioning
confidence: 99%
“…Absorbance was measured using a DTX880 multi-mode microplate reader (Beckman Coulter, Pasadena, CA, USA). IgA, GC and HSP70 concentrations were calculated using SoftMax pro software (Molecular Devices, LLC, San Jose, CA, USA) as described previously [54,55]. The IgA flow rate in saliva (µg/min/g SMG tissue) was calculated by multiplying the absolute concentration of IgA (µg/mL) by the saliva flow rate (mL/min) as per g of SMG tissue.…”
Section: Elisamentioning
confidence: 99%
“…However, neither can we confirm that dark chocolate-mediated cognitive enhancements are unrelated to NGF and BDNF levels in the human brain, since we are not able to determine the levels of NGF and BDNF in the human brain following dark chocolate intake. However, theobromine—which dark chocolate is rich in—was found to increase the level of BDNF in mouse and rat brains [14,19], implying that dark chocolate may upregulate NGF and/or BDNF in the human brain and improve cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in intracellular cAMP level activates the cAMP-response element-binding protein (CREB), which in turn, leads to the expression of the brain-derived neurotrophic factor (BDNF), one of the neurotrophins that mediates neuronal functions such as learning and memory. We also recently showed that theobromine-fed mice and rats performed better in memory tasks in a CREB/BDNF pathway-dependent manner [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides flavanols, theobromine and other methylxanthines, peptides [8], and volatile aroma compounds [9] might also affect human health, e.g., theobromine, which seems to improve memory in rats [10]. Many studies, being intervention studies or epidemiological observations, do not focus on single compounds, but on cocoa as such; in some cases, enriched in polyphenols.…”
mentioning
confidence: 99%